2017
DOI: 10.21448/ijsm.376691
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Effects of Methanol Extracts of Some Plant Species Belonging to Lamiaceae Family

Abstract: Species belonging to Lamiaceae family are used as an antibacterial agent among medical plants. The aim of the present study was to determinate the antibacterial effects of the methanolic extracts of some plant species belonging Lamiaceae family which distributed to different ecological conditions in Amasya. The antibacterial effects of Stachys annua, Scutellaria salviifolia and Nepata nuda plant extracts were determined by disc diffusion and micro dilution methods. The antibacterial effects of plant extracts w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…In that study, the antibacterial activity of methanol extract obtained from aerial parts of S. salviifolia along with some species from Lamiaceae family was investigated against S. aureus, E. coli, Klebsiella pneumoniae, P. aeruginosa and S. enteritidis by using microdilution method in concentrations between 6.25 mg/ml-50 mg/ml. According to the results of that study, among the tested extracts, S. salviifolia was found to possess the highest antibacterial activity with 12.5 mg/ml MIC value against S. aureus, S. enteritidis and E. coli and with 25 mg/ml MIC value against K. pneumoniae and P. aeruginosa [18]. In our study, we have found that S. salviifolia exhibited antibacterial activity against S. aureus, E. faecalis, E. coli and, P. aeruginosa with a 1024 μg/ml MIC value.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…In that study, the antibacterial activity of methanol extract obtained from aerial parts of S. salviifolia along with some species from Lamiaceae family was investigated against S. aureus, E. coli, Klebsiella pneumoniae, P. aeruginosa and S. enteritidis by using microdilution method in concentrations between 6.25 mg/ml-50 mg/ml. According to the results of that study, among the tested extracts, S. salviifolia was found to possess the highest antibacterial activity with 12.5 mg/ml MIC value against S. aureus, S. enteritidis and E. coli and with 25 mg/ml MIC value against K. pneumoniae and P. aeruginosa [18]. In our study, we have found that S. salviifolia exhibited antibacterial activity against S. aureus, E. faecalis, E. coli and, P. aeruginosa with a 1024 μg/ml MIC value.…”
Section: Resultsmentioning
confidence: 93%
“…The antioxidant activity of the methanol and ethyl acetate extracts of these taxa by using DPPH and FRAP assays was also determined in the same study [17]. Antibacterial effects of methanol extracts prepared from the leaves, stems and flowers of S. salviifolia were also investigated [18].…”
mentioning
confidence: 99%
“…In a study conducted in 2017, antimicrobial activity of S. salviifolia methanol extract was tested with the disc diffusion and microdilution methods. MIC results of methanol extract varied between 12,5-25 mg/ml against E. coli, K. pneumoniae, S. enteritidis P. aeruginosa, S. aureus [27]. Arıtuluk et al (2019) found that aqueous, methanol and n-butanol extracts from roots and methanol and n-butanol extracts from aerial parts of S. salviifolia, S. diffusa and S. pontica and n-hexane extracts from root parts of S. diffusa showed low or no antibacterial activity (1024 μg/ml).…”
Section: Antimicrobial Activity Resultsmentioning
confidence: 98%
“…They concluded that the essential oil of N. cataria can be used as a natural protective agent on food products. Yavuz et al [15] reported that the methanol extract of N. nuda can be evaluated as a potent good antimicrobial agent on 5 bacteria. Çelik et al [23] B-4375 by using the disc diffusion method.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…In addition, recent antimicrobial activity studies on Nepeta species have been reported to be a natural preservative and a strong antimicrobial agent on food products. [14,15]. In this work, we aimed to investigate chemical composition of essential oil and in vitro biological activities of endemic N. cadmea species in Turkey.…”
Section: Introductionmentioning
confidence: 99%